If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2m-6)=-6
We move all terms to the left:
-3(2m-6)-(-6)=0
We add all the numbers together, and all the variables
-3(2m-6)+6=0
We multiply parentheses
-6m+18+6=0
We add all the numbers together, and all the variables
-6m+24=0
We move all terms containing m to the left, all other terms to the right
-6m=-24
m=-24/-6
m=+4
| (4x+10)=50+(x+5) | | 4(2x+2)-4x=48 | | 73.5=6s^2 | | 3.5n/7=1/7 | | (5x+6)=(3x+7) | | 4(1-8x)=29-7x | | 2x=27=2x-11 | | 32.00+9.25x+15.00=124.25 | | 2x-(-11)=12 | | 9(3a-7)=-2a-15-4a | | 6y–1=2(3–y) | | 7x-1+11x-29=180 | | 6x+155=445 | | -4(y+6)+y=9 | | 7+3(6x+3)=52 | | 14x+15=192 | | 6a^2+14-5a=0 | | 5(e+6=75 | | 8x4=23-11 | | 27=7(x)+6 | | 3(x–7)+4=28–2x | | a−37=2/7 | | 8x2+20x+12=0 | | a−3/7=2/7 | | 2(x-4)+3=13-4x | | x^2-5x+43=57 | | -4s+8s+2=125 | | p=31/6=-21/2 | | −1+a=-6 | | 12+37x=−15 | | 40=3.10x+5.00 | | -15x-5=10x+25 |